Empowering ESL Learning: Motivation in Acquiring English as a Second Language - Dela Rosa, Reyn Alyana Legaspi; Santos, Crissel Kylle; Yaya, Kristan (LPPM STIKI Malang, 2024)
ABSTRACT: This study investigates the role of motivation in enhancing English as a Second Language (ESL) acquisition among Grade 7 students. It employs a qualitative-descriptive method as it analyzes the complex dynamics of motivation in the context of English as a Second Language (ESL) learning, providing a nuanced grasp of the motivational elements that influence ESL learners' language acquisition journeys. The study investigates the varied nature of motivation using interviews and thematic analysis, with the goal of uncovering ESL learners' subjective experiences, challenges, and attitudes. Grasping the complexities of motivation within the ESL context is dominant, as it can influence students' engagement and language proficiency. Results of the study have shown that English as a Second Language Learning (ESL) is one of the common factors that affects students learning in a classroom setting. Motivation also plays a significant role in determining students’ academic performance and overall accomplishment in acquiring proficiency in English as a Second Language (ESL). The study assessed the motivational factors among Grade 7 students, focusing on Integrative Orientation with a composite mean of (5.14) and Instrumental Orientation with a composite mean (5.07) respectively. Problems encountered were evaluated through Survey Questionnaires (composite mean: 3.65) and Interviews. Integrative Orientation significantly influences English as a Second Language motivation, while difficulties in English language usage emerge as primary issues. Grade 7 students, undergoing a transitional academic phase, face challenges in adjusting to learning. Recommendations of the researchers focus on academic importance that will help enhance and increase learning motivation of the students in English as a Second Language.